Analyzing the Economic Feasibility of Circular Economy Practices in Natural Resource Utilization - Syamsu Rijal; Muhammad Nur Afiat; Mustari (Citakonsultindo, 2026)
The transition from a linear, extractive economy to a circular economy is crucial for Indonesia, a resource-rich country, in maintaining long-term economic resilience. This study aims to analyze the economic feasibility of circular economy practices in natural resource utilization in Indonesia using a longitudinal approach over a decade (2014–2024). The methodology used is descriptive quantitative with Net Present Value (NPV) analysis, Internal Rate of Return (IRR), and the integration of Green Accounting to monetize environmental externalities. The results show that circular economy projects in the downstream mineral and plantation sectors reach break-even on average within 4.5-6 years, with an increase in operational efficiency of 18–25% through waste reduction and raw material substitution. The novelty of this study lies in the use of 10-year time-series data, which validates that circularity significantly reduces the company's financial risk profile to global commodity price volatility. The implications of this study emphasize the need to standardize secondary material prices and to implement more aggressive fiscal incentives to accelerate the national green economy transformation.